2020
DOI: 10.1021/acsnano.0c04936
|View full text |Cite
|
Sign up to set email alerts
|

Intratesticular Peptidyl Prolyl Isomerase 1 Protein Delivery Using Cationic Lipid-Coated Fibroin Nanoparticle Complexes Rescues Male Infertility in Mice

Abstract: Male infertility is a multifactorial condition. Unexplained male infertility is often caused by spermatogenesis dysfunction. Knockout of Pin1, an important regulator of cell proliferation and differentiation, produces male infertility phenotypes such as testicular immaturity and azoospermia with spermatogonia depletion and blood−testis barrier (BTB) dysfunction. Gene therapy has been clinically considered for the treatment of male infertility, but it is not preferred because of the risks of adverse effects in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 83 publications
0
8
0
1
Order By: Relevance
“…For example, Kim et al developed a nanoparticle complex with PIN1 proteins inside to treat infertile mice that were lacking the PIN1 protein. These experiments successfully restore the fertility of the mice [ 70 ]. It has recently been suggested that proteins offer advantages over other small molecules regarding their use as therapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Kim et al developed a nanoparticle complex with PIN1 proteins inside to treat infertile mice that were lacking the PIN1 protein. These experiments successfully restore the fertility of the mice [ 70 ]. It has recently been suggested that proteins offer advantages over other small molecules regarding their use as therapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
“…PIN1 has also been pinpointed as a seminal biomarker for higher fertility in porcine models [ 43 ]. Finally, we wish to highlight a recent study where the intracellular injection of PIN1 lipid nanoparticles in knockout mice ( Pin1 −/− ) resulted in the regulation of spermatogonial proliferation and differentiation and in the restructuring of the BTB, thus rescuing fertility in male mice [ 44 ]. Therefore, we consider that our findings encourage the analysis of PIN1 as a therapeutic target to restore human male fertility.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic deletion of PIN1 may lead to testicular atrophy and a consequent reduction in fertility ( 31 ). Recent studies showed that PIN1 participates in the maintenance of BTB function and integrity by regulating the expression of junction proteins between SCs: connexin43 (Cx43; gap junction) and N-cadherin (CDH2; adhesion junction), and its deficiency results in the destruction of BTB integrity ( 32 , 33 ). In the present study, PIN1 was identified as having a significantly increased abundance in postpubertal testes, a finding suggestive of an active role for the PIN1 gene in BTB function during sheep spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%